Altered predictive contextual processing of emotional faces versus abstract stimuli in adults with Autism Spectrum Disorder. Issue 6 (June 2019) - Fogelson, Noa; Li, Ling; Diaz-Brage, Pablo; Amatriain-Fernandez, Sandra; Valle-Inclan, Fernando
Highlights: Processing of predictive context is altered in adults with Autism Spectrum Disorder (ASD). Abnormalities are more pronounced for emotional cartoon faces versus abstract triangles. Predictive context processing in ASD is associated with weaker fronto-parietal connectivity. Abstract: Objectives: We investigated the proposition that Autism Spectrum Disorder (ASD) is associated with predictive contextual processing deficits. Methods: We recorded electroencephalography (EEG) in adults with ASD and controls during the performance of a predictive contextual processing task, using either triangles or emotional faces. Targets were preceded by either randomized sequences (R) or by sequences including a predictive sequence (P). Results: ASD subjects showed an attenuated behavioral facilitation (P versus R) compared with controls (faces). P3b amplitudes of P, R and the predictive sequence (n-1) were attenuated in ASD compared with controls. However, the attenuation of n-1 was more pronounced during the processing of faces. Controls demonstrated shorter peak P3b latencies of P versus R, while this facilitation was absent in ASD subjects. ASD subjects demonstrated functional connectivity alterations during the processing of random (triangles and faces) and predicted targets (faces). These changes were associated with weaker, more randomised, functional connections between frontal and parietal regions in ASD. Conclusions: We found predictive contextual processing alterations in ASD, which were more pronounced during the processing of emotional faces compared with abstract stimuli. Significance: We provide novel evidence for the proposition that ASD is associated with deficits of top-down predictions.